2022
DOI: 10.3389/fcell.2022.919637
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated ENC1 predicts unfavorable prognosis and correlates with immune infiltration in endometrial cancer

Abstract: A better knowledge of the molecular process behind uterine corpus endometrial carcinoma (UCEC) is important for prognosis prediction and the development of innovative targeted gene therapies. The purpose of this research is to discover critical genes associated with UCEC. We analyzed the gene expression profiles of TCGA-UCEC and GSE17025, respectively, using Weighted Gene Co-expression Network Analysis (WGCNA) and differential gene expression analysis. From four sets of findings, a total of 95 overlapping gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Early diagnosis is often associated with better cancer prognosis since middle- and advanced-stage patients with cancer tend to have poor outcomes. Abundant evidence suggests that inhibiting oncogenes or enhancing the expression of tumor suppressor genes improves the survival time of patients with cancer [ 13 , 15 , 17 , 18 ]. For instance, Yan et al [ 17 ] reported that overexpressing microsomal glutathione S-transferase 1 (MGST1), which is associated with histological type of tumor, hormone therapy, and tumor immune cell infiltration, was linked to better survival outcomes in patients with UCEC.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is often associated with better cancer prognosis since middle- and advanced-stage patients with cancer tend to have poor outcomes. Abundant evidence suggests that inhibiting oncogenes or enhancing the expression of tumor suppressor genes improves the survival time of patients with cancer [ 13 , 15 , 17 , 18 ]. For instance, Yan et al [ 17 ] reported that overexpressing microsomal glutathione S-transferase 1 (MGST1), which is associated with histological type of tumor, hormone therapy, and tumor immune cell infiltration, was linked to better survival outcomes in patients with UCEC.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that ENC1 also was one of the key genes involved in the pathogenesis of Alzheimer's disease ( 19 ). He et al found that upregulated ENC1 predicts unfavorable prognosis and correlates with immune infiltration in endometrial cancer ( 8 ). Further investigation of ENC1 is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the expression of ENC1 is significantly increased in breast cancer compared with normal breast tissue, and is significantly associated with the proliferation, migration, and invasion of breast cancer cells ( 7 ). A study on cervical cancer patients showed that the higher the ENC1 expression level in cancer tissues, the worse the prognosis ( 8 ). Based on the few studies on the effect of ENC1 on gastrointestinal tumors, this study aimed to investigate the expression, clinical significance, and prognosis of ENC1 in gastrointestinal tumors by analyzing the data in The Cancer Genome Atlas (TCGA), providing a new target for the precise treatment of gastrointestinal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…It has primarily been investigated for its role as a regulator of the transcription factor Nrf2 in the oxidative stress response [8]. Previous studies have also shown that it plays a key role in neuronal and adipocyte differentiation, and is involved in many biological processes in cancer, including ovarian cancer [9], endometrial cancer [10], and lung cancer [11]. Interestingly, it is highly expressed in brain tissues including the frontal cortex, cortex and anterior cingulate cortex, and hippocampus compared to other tissues (GTEx, https://gtexportal.org/home/).…”
Section: Introductionmentioning
confidence: 99%